Optimised versus standard dosing of vancomycin in infants with Gram-positive sepsis (NeoVanc): a multicentre, randomised, open-label, phase 2b, non-inferiority trial - Hill, L; Clements, MN; Turner, MA; Dona, D; Lutsar, I; Jacqz-Aigrain, E; Heath, P; Roilides, E; Rawcliffe, L; Alonso-Diaz, C; Baraldi, E; Dotta, A; et al. (Elsevier, 2021)
Background: Vancomycin is the most widely used antibiotic for neonatal Gram-positive sepsis, but clinical outcome data of dosing strategies are scarce. The NeoVanc programme comprised extensive preclinical studies to inform a randomised controlled trial to assess optimised vancomycin dosing. We compared the efficacy of an optimised regimen to a standard regimen in infants with late onset sepsis that was known or suspected to be caused by Gram-positive microorganisms.